Estudio del Mercado Potencial de profesionales de los hospitales Carlos Andrade Marín y Baca Ortiz de la ciudad de Quito, afines a la Maestría en Intervención, Asesoría y Terapia Familiar Sistémica (MIATEFAS), creación y construcción de la demanda de estudios de postgrado. - Trujillo Arboleda, Aurea (2010)
When we set out to make the thesis of the Study of the Potential Market Professionals for entry into the MIATEFAS (Master of Intervention, Counseling and Systemic Family Therapy), we stand facing a challenge that apparently left the specific logical framework and possibly proposing the ultimate goal of training is to build harmonious relations between human beings in search of a comprehensive, full life and solidarity. It seemed that the theoretical and operational marketing budgets, to call with a nonsensical name among many social scientists still seemed a close subject with our searches and career goals, however, as the problems were discovered interiorizándonos in any human activity that it is outside relationships, interactions, transactions, links, functions and dysfunctions and therefore it was possible to have a systemic approach to understanding other perspectives.